Controls of hydrocarbon generation on the development of expulsion fractures in organic-rich shale: Based on the Paleogene Shahejie Formation in the Jiyang Depression, Bohai Bay Basin, East China. (September 2017) - Ma, Cunfei; Elsworth, Derek; Dong, Chunmei; Lin, Chengyan; Luan, Guoqiang; Chen, Bingyi; Liu, Xiaocen; Muhammad, Jawad Munawar; Muhammad, Aleem Zahid; Shen, Zhengchun; Tian, Fuchun
Abstract: The development of expulsion fractures in organic-rich shale is closely related to hydrocarbon generation and expulsion from kerogen. Organic-rich shales from the upper part of the fourth member and the lower part of the third member of the Paleogene Shahejie Formation in the Jiyang Depression, Bohai Bay Basin, East China, are used as an example. Based on thin sections, SEM and thermal simulation experiments, the characteristics of hydrocarbon generation and the conditions supporting the development of expulsion fractures were explored. The key factors influencing these fractures include the presence of kerogens, their distribution along laminae and around particle boundaries, their exposure to heat and the build-up in pressure due to confinement by low permeability. The development of excess pore fluid pressures and intrinsic low rock fracture strength are the main influencing factors. Pressurization by rapid generation of hydrocarbon provides impetus for fracture initiation and cause bitumen to migrate quickly. The shale laminae results in distinctly lower fracture strength laminae-parallel than laminae-normal and this directs the formation of new fractures in the direction of weakness. When pore fluid pressure increases, maximum and minimum principal effective stresses decrease by different proportions with a larger reduction in the maximum principal effective stress. This increases the deviatoric stress and reduces the mean stress, thus driving the rock towards failure. Moreover, the tabular shape of the kerogen aids the generation of hydrocarbon and the initiation of expulsion fractures from the tip and edge. The resulting fractures extend along the laminae when the tensile strength is lower in the vertical direction than in the horizontal direction. Particle contact boundaries are weak and allow fractures to expand around particles and to curve as the stress/strength regime changes. When pore fluid pressure fields at different fracture tips overlap, fractures will propagate and interconnect, forming a network. This paper could provide us more detailed understanding of the forming processes of expulsion fractures and better comprehension about hydrocarbon expulsion (primary migration) in source rocks. Graphical abstract: Highlights: Expulsion fractures initiate from kerogen, extend parallel to laminae, curve at the end and finally form a fracture network. Thermal simulation experiments show expulsion fractures enhances with the increase of temperature and pressure. Pore fluid pressure and rock's fracture strength are the main influencing factors on the origin of expulsion fractures.